Close the Book on Hate 101 Ways To Combat Prejudice. (Distributed by ERIC Clearinghouse, 2001)
This pamphlet, which is part of the Close the Book on Hate Campaign, provides definitions, resources, and suggested readings on combating prejudice. The premise of the campaign is the belief that through reading and discussion, children will be better able to counter prejudice and hate. The pamphlet begins with suggestions for combatting prejudice at home (e.g., get to know and take pride in one's heritage and share it with others); at school (e.g., establish a diversity club and create a school anti-prejudice slogan); in the workplace (e.g., make respect for diversity a core value with the company and become aware and respectful of individual work styles); in houses of worship (e.g., urge leaders to use the pulpit to condemn all forms of bigotry); and in the community (e.g., establish a Human Rights Commission and a Community Watch Group). The pamphlet presents common definitions of relevant terms; offers response strategies (e.g., notify law enforcement and reach out to victims); explains how to plan ahead (e.g., work with school, community, and law enforcement officials to establish a plan for responding promptly to hate crimes); and offers a reading list and a list of allies. (SM)